Peran Guru BK melalui Layanan Penguasaan Konten menggunakan Media Mind Mapping untuk Meningkatkan Daya Ingat Siswa Kelas X SMA Swasta Pelita Bulu Cina - Sefira, Vira (Lembaga Yasin AlSys, 2025)
This study is motivated by the low memory retention among students, as indicated by difficulties in recalling information, answering questions, and comprehending learning materials comprehensively. The objective of this research is to describe the role of Guidance and Counseling (BK) teachers in enhancing students’ memory retention through content mastery services supported by mind mapping media. A descriptive qualitative approach was employed, conducted at SMA Swasta Pelita Bulu Cina. The research subjects consisted of one BK teacher and ten Grade X students, selected purposively for their direct involvement in the implementation of the service. Data were collected through observation, interviews, and documentation, and analyzed using the stages of data reduction, data display, and conclusion drawing, with source triangulation used for validation. The findings show that content mastery services assisted by mind mapping are effective in improving students’ conceptual understanding, information organization, and memory retention, particularly among students with visual and kinesthetic learning styles. The use of mind mapping also enhanced student engagement and motivation. However, challenges emerged, including difficulty in drawing, confusion in structuring complex information, and limited suitability for technical subjects. The study concludes that BK teachers play a strategic role in designing and implementing innovative, student-centered learning support services. The implications highlight the need for ongoing training and collaboration with subject teachers to ensure optimal implementation of mind mapping-based content mastery services in improving learning quality and memory retention.